Synthesis of 2-[4-(10H-Substituted Phenothiazine-3-yl)-6-Pyrimidin-2-Phenylthiol/ol/amine/thiol] Pyrroles - Narule, Meghasham; Meshram, Jyotsna S.; Santhakumari, B.; Shanware, A. (E-Journal of Chemistry, 2007)
2-[4-Hydroxy benz-1(propene-1-one)]Pyrrole II on treatment with phenyl thiourea, guanidine carbonate, urea and thiourea in alcoholic KOH yielded compounds III, IV, V, VI which on treatment with different aryl anilines gave compounds VII, VIII, IX, X which under goes cyclisation with sulphur and iodine to give 2-[4-(10H-substituted phenothiazine-3-yl)-6-pyrimidin-2-phenylthiol/-ol/-amine/-thiol] pyrrole XI(a-j), XII(a-j), XIII(a-j) and XIV(a-j) respectively. The structural products were characterized by elemental analysis and spectral data.

Serum responsive proteome reveals correlation between oxidative phosphorylation and morphogenesis in Candida albicans ATCC10231 - Ahmed, Radfan; Kodgire, Santosh; Santhakumari, B.; Patil, Rajendra; Kulkarni, Mahesh J.; Zore, Gajanan (Journal of Proteomics, 2018)
To understand the impact of fetal bovine serum (FBS) on metabolism and cellular architecture in addition to morphogenesis, we have identified FBS responsive proteome of Candida albicans. FBS induced 34% hyphae and 60% pseudohyphae in C. albicans at 30 C while 98% hyphae at 37 C. LC-MS/MS analysis revealed that 285 proteins modulated significantly in response to FBS at 30 degrees C and 37 degrees C. Out of which 152 were upregulated and 62 were downregulated at 30 degrees C while 18 were up and 53 were downregulated at 37 degrees C. Functional annotation suggests that FBS may inhibit glycolysis and fermentative pathway and enhance oxidative phosphorylation (OxPhos), TCA cycle, amino acid and fatty acid metabolism indicating a use of alternative energy source by C. albicans. OxPhos inhibition assay using sodium azide corroborated the correlation between inhibition of glycolysis and enhanced OxPhos with pseudohyphae formation. C. albicans induced hyphae in response to FBS irrespective of down regulation of Rasl,Asrl/Asr2, indicates the possible involvement of MAPK and cAMP-PKA independent pathway. The Cell wall of cells grown in presence of FBS at 30 degrees C was rich in mannan, Beta 1,3glucan and chitin while membranes were rich in ergosterol compared to those grown at 37 degrees C. Significance of the study: This is the first study suggesting a correlation between OxPhos and morphogenesis especially pseudohyphae formation in C. albicans. Our data also indicate that fetal bovine serum (FBS) induced morphogenesis is multifactorial and may involve MAPK and cAMP-PKA independent pathway. In addition to morphogenesis, our study provides an insight in to the modulation of metabolism and cellular architecture of C. albicans in response to FBS.
Keywords: analysis; Candida albicans; Fetal bovin serum; Liquid chromatography mass spectrometry; morphogenesis; Oxidative phosphorylation; pathogenicity

Streptomyces sp metabolite(s) promotes Bax mediated intrinsic apoptosis and autophagy involving inhibition of mTOR pathway in cervical cancer cell lines - Dan, Vipin Mohan; Muralikrishnan, Balaji; Sanawar, Rahul; Vinodh, J. S.; Burkul, Bhushan Bapusaheb; Srinivas, Kalanghad Puthankalam; Lekshmi, Asha; Pradeep, N. S.; Dastager, Syed G.; Santhakumari, B.; Santhoshkumar, Thankayyan R.; Kumar, R. Ajay; et al. (Scientific Reports, 2018)
In cervical cancer, the association between HPV infection and dysregulation of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway (PI3K/AKT/mTOR pathway) places mTOR as an attractive therapeutic target. The failure of current treatment modalities in advanced stages of this cancer and drawbacks of already available mTOR inhibitors demand for novel drug candidates. In the present study we identified the presence of a mTOR inhibitor in an active fraction of the ethyl acetate extract of Streptomyces sp OA293. The metabolites(s) in the active fraction completely inhibited mTORC1 and thereby suppressed activation of both of its downstream targets, 4E-BP1 and P70S6k, in cervical cancer cells. In addition, it also stalled Akt activation via inhibition of mTORC2. The mechanism of mTOR inhibition detailed in our study overcomes significant drawbacks of well known mTOR inhibitors such as rapamycin and rapalogs. The active fraction induced autophagy and Bax mediated apoptosis suggesting that mTOR inhibition resulted in programmed cell death of cancer cells. The molecular weight determination of the components in active fraction confirmed the absence of any previously known natural mTOR inhibitor. This is the first report of complete mTOR complex inhibition by a product derived from microbial source.

SWATH-MS reveals that bisphenol A and its analogs regulate pathways leading to disruption in insulin signaling and fatty acid metabolism - Kulsange, Shabda E.; Sharma, Monika; Sonawane, Babasaheb; Jaiswal, Meera R.; Kulkarni, Mahesh J.; Santhakumari, B. (Food and Chemical Toxicology, 2024)
Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC), associated with obesity and insulin resistance. The FDA prohibited the use of BPA-based polycarbonate resins in infant formula packaging; thus, its analogs, viz. Bisphenol S (BPS) and Bisphenol F (BPF) were considered alternatives in epoxy resins, plastics, and food cans. As these analogs might evoke a similar response, we investigated the role of Bisphenols (BPA, BPF, and BPS), on insulin signaling in CHO-HIRc-myc-GLUT4eGFP cells at environmentally relevant concentrations of 2 nM and 200 nM. Insulin signaling demonstrated that Bisphenols reduced phosphorylation of IR and AKT2, GLUT4 translocation, and glucose uptake. This was accompanied by increased oxidative stress. Furthermore, SWATHMS-based proteomics of 3T3-L1 cells demonstrated that Bisphenol-treated cells regulate proteins in insulin resistance, adipogenesis, and fatty acid metabolism pathways differently. All three Bisphenols induced differentially expressed proteins enriched similar pathways, although their abundance differed for each Bisphenol. This might be due to their varying toxicity level, structural differences, and estrogen-mimetic activity. This study has important implications in addressing health concerns related to EDCs. Given that the analogs of BPA are considered alternatives to BPA, the findings of this study suggest they are equally potent in altering fatty acid metabolism and inducing insulin resistance.
Keywords: Bisphenols; Estrogen; Lipid droplet; Mitochondrial beta-oxidation; Oxidative stress; PPAR gamma